2022
DOI: 10.3390/su14063466
|View full text |Cite
|
Sign up to set email alerts
|

Deconstruction of the Green Bubble during COVID-19 International Evidence

Abstract: Bubbles are usually chaotic but can be predictable, provided their formation matches the log periodic power law (LPPL) with unique stylized facts. We investigated Green Bubble behaviour in the stock prices of a selection of stocks during the COVID-19 pandemic, namely, those with the highest market capitalization from a basket of North American and European green energy or clean tech companies and the S&P Global Clean Energy Index. Moreover, the biggest Exchange Traded Fund (TAN) by market capitalization wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…As suggested by other authors, a drawdown is defined as a sharp move from local minima to local maxima (Ghosh et al, 2021; Ghosh, Papathanasiou, Dar, & Kenourgios, 2022). Previous analysis has shown that the worst 10 drawdowns between 1970 and 2020, on average, exhibited a 27% drop.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As suggested by other authors, a drawdown is defined as a sharp move from local minima to local maxima (Ghosh et al, 2021; Ghosh, Papathanasiou, Dar, & Kenourgios, 2022). Previous analysis has shown that the worst 10 drawdowns between 1970 and 2020, on average, exhibited a 27% drop.…”
Section: Resultsmentioning
confidence: 96%
“…The data set selection is not arbitrary. The LPPL methodology requires the data set to include drawdowns (Ghosh, Papathanasiou, Dar, & Kenourgios, 2022). Previous studies have suggested that the average drawdown should be more than 50% in cryptocurrencies to sustain the crash.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, some studies have underlined that analysis between the two markets should be of a dynamic nature, as the relation between them changes at different moments in time and according to the context conditions, which are also of a variable nature (Broadstock and Filis, 2014; Sadorsky, 2014; Antonakakis et al , 2017; Anand and Sunil, 2021). For their part, analysing a selection of stocks during the COVID-19 pandemic and the S&P Global Clean Energy Index, Ghosh et al (2022) argue that green and sustainable finance offers benefits and opportunities for stock exchanges, especially for energy stocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, Ghosh et al [17] proved that, unlike conventional bubbles, the effects of green (Green finance refers to "the flow of financial investments into sustainable development projects and initiatives, environmental products, and policies that encourage the development of a more sustainable economy" [17]) bubbles are not detrimental since they boost infrastructure expenditure and economic activity, which is good for overall growth. Moreover, Umar et al [18] reported that markets adhering to ESG criteria are interconnected, with their connectivity significantly increasing during unrest such as the European sovereign debt crisis, the systemic Greek difficulties, and the coronavirus pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%